Why Firms Lay Off Workers Instead of Cutting Wages: Evidence from Linked Survey-Administrative Data - Antoine Bertheau; Marianna Kudlyak; Birthe Larsen; Morten Bennedsen (Institute of Labor Economics (IZA), 2025)
We use a novel large-scale survey of firms, implemented in Denmark in 2021 and linked to administrative data, to study why firms lay off workers instead of cutting wages. Our questions on layoffs, wage cuts, and the link between them provide new insights into firms' strategies for adjusting labor in response to adverse shocks. We find that layoffs are more prevalent than wage cuts, but wage cuts are not rare in firms experiencing revenue reduction and were used by 15% of such firms. Employers are hesitant to cut wages in many instances because they see wage cuts as a poor substitute for layoffs. First, firms report that lowering wages triggers costs through the impact on morale and quits. Comparing these costs with potential savings from wage cuts, most employers in the survey agree that a wage reduction would not have saved jobs. Second, firms report that a crisis is an opportune time for layoffs because of lower opportunity costs of restructuring and because layoffs during a crisis are perceived by workers as more fair. We find that firms that report such opportunistic layoffs are less likely to implement wage cuts.
Keywords: D22; J30; J63; J23; 330; wage rigidity; layoffs